2019
DOI: 10.3311/ppch.12519
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanogel Design on Gymnema sylvestre Essential Oils to Inhibit Growth of Candida albicans Biofilm and Investigation of Gene Expression ALS1, ALS3

Abstract: Chitosan (CS) is a polycation with a pka of about 6.3 with a charge density dependent on pH and the %DA-value which can interact with polyanions to form complex and gels. Nanoparticles (CNPs) in addition can increase the antifungal potential of bioactive compounds like essential oils by increasing cellular interactions between them and the fungal as a result of the very small size that enhances cellular uptake. In this study, was set to investigate the encapsulation of the Gymnema sylvestre essential oils (G.E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…4. To evaluate the structure of the matrix of medicines, the functional groups are analyzed with the help of literature [32][33][34][35][36][37][38]. FT-IR absorption peaks associated with the corresponding bands are given in Table 4.…”
Section: Ftir Analysismentioning
confidence: 99%
“…4. To evaluate the structure of the matrix of medicines, the functional groups are analyzed with the help of literature [32][33][34][35][36][37][38]. FT-IR absorption peaks associated with the corresponding bands are given in Table 4.…”
Section: Ftir Analysismentioning
confidence: 99%
“…One such example is chitosan (CS), a natural cationic polysaccharide with inherent antibacterial activity and favorable biological compatibility . Prepared by the partial or full deacetylation of chitin, the amino groups in CS have a pKa value of ∼6.3, enabling it to readily bind to the negatively charged surfaces of both bacteria and MoS 2 . Moreover, the incorporation of CS not only changes the surface charge of the modified materials so as to enhance the bactericidal efficacy, but also improves the biocompatibility of the resultant composites.…”
Section: Introductionmentioning
confidence: 99%
“…The ndings demonstrated that this CS nanogel exhibited fungicidal properties against the Candida albicans strain while also inhibiting its formation of biolms. 56 Moreover, further studies have shown that CS-based nanogels encapsulating essential oils enhanced both the antimicrobial effectiveness, specically leading to higher antifungal activity, and stability of the oils, facilitating their utilization within the food industry. [57][58][59] Therefore, CS-based nanogels have remarkable potential in various biomedical applications including antibiolm therapeutics.…”
Section: Chitosan-based Nanogels For Biolm Therapymentioning
confidence: 99%
“…Studies have investigated their potential beyond antibacterial activities, focusing on their efficacy in controlling fungal growth. For instance, Akbari et al 56 created a nanogel by combining CS and myristic acid and incorporating Gymnema sylvestre oil. The aim was to enhance the stability and antifungal efficacy against Candida albicans strain (ATCC 10231).…”
Section: Nanogels For Biofilm Therapymentioning
confidence: 99%